An Analysis of Politeness Strategies in A Youtube Interview with Anies Baswedan - Apriani Joni; Magvirah Octasary; Hujaefah Hi Muhamad (Cakrawala Bahasa, 2026)
This study aims to analyze the types of politeness strategies used by Anies Baswedan in a YouTube interview on the podcast What Is Up Indonesia? Episode “The Fault in Our Education, Political Islam, and Gen Alpha Slang.” The study also investigates how these politeness strategies reflect his communication style as a public figure. This research used a qualitative descriptive method with a pragmatic approach. The data were collected from the transcript of the interview video uploaded on YouTube. The researcher analyzed the utterance using Brown and Levinson’s (1987) theory of politeness strategies, focusing on positive politeness and negative politeness. The findings show that Anies Baswedan frequently used positive politeness strategies such as exaggerate, intensify interest to hearer, seeking agreement, avoiding disagreement, joking, including both speaker and hearer in the activity and giving reasons. In addition several negative politeness strategies were also identified, including the use of questions and pessimiistice expressions. The findings indicate that Anies Baswedan tends to create a friendly, respectfull, and inclusive atmosphere during communication. His politeness strategies in digital political communication.